2017
DOI: 10.5433/1679-0359.2017v38n2p801
|View full text |Cite
|
Sign up to set email alerts
|

Parasitological analysis of green leaf lettuce cultivated in different production systems

Abstract: This study analysed parasite contamination in green leaf lettuce (Lactuca sativa), grown in different cultivation systems (conventional, organic, and hydroponic), from a family farmer cooperative in the municipality of Presidente Prudente, São Paulo, Brazil. Samples were collected at weekly intervals during five months, totalling 180 vegetable samples (60 samples of leaf lettuce from each cultivation system). Lettuce leaves were washed with 0.5% Extran MA 02, and the resulting fluid subjected to sedimentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…An elevated number of intestinal parasites was detected in foliar vegetables commercialized in Aparecida de Goiânia, especially lettuce. The index of 70% positivity of lettuce samples is very high comparing with several others studies carried out in Brazil (Esteves and Figueirôa, 2009;Neres et al, 2011;Fernandes et al, 2015;Silva et al, 2015;Moura et al, 2016;Santos et al, 2017;Machado et al 2020); the nematode larvae were not included in statistics because they were not identified at the family, genus or species Occurrence of enteroparasites in foliar vegetables level, as they could be larvae of free-living non-parasitic nematodes. In addition, probable trematode eggs and Trypanoxyuris sp.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…An elevated number of intestinal parasites was detected in foliar vegetables commercialized in Aparecida de Goiânia, especially lettuce. The index of 70% positivity of lettuce samples is very high comparing with several others studies carried out in Brazil (Esteves and Figueirôa, 2009;Neres et al, 2011;Fernandes et al, 2015;Silva et al, 2015;Moura et al, 2016;Santos et al, 2017;Machado et al 2020); the nematode larvae were not included in statistics because they were not identified at the family, genus or species Occurrence of enteroparasites in foliar vegetables level, as they could be larvae of free-living non-parasitic nematodes. In addition, probable trematode eggs and Trypanoxyuris sp.…”
Section: Discussionmentioning
confidence: 78%
“…Despite the undeniable nutritional importance, raw or poorly washed vegetables contaminated with fecal residues or irrigated with water contaminated with parasitic forms have been reported as important vehicles for transmission of intestinal parasites to humans (Andrade et al, 2010;Fernandes et al, 2015). In Brazil, contamination of foliar vegetables is one of the main transmission routes of enteroparasites to humans (Soares and Cantos, 2005;Neres et al, 2011), and several studies have confirmed the presence of parasitic forms in vegetables commercialized in all regions of the country (Soares and Cantos, 2005;Esteves and Figueirôa, 2009;Neres et al, 2011;Gomes et al, 2014;Fernandes et al, 2015;Silva et al, 2015;Novacki et al, 2016;Santos et al, 2017;Maldonade et al, 2019;Machado et al, 2020;Rodrigues et al, 2020). However, in the State of Goiás there are still few reports on the occurrence of vegetables contaminated with parasitic forms.…”
Section: Resultsmentioning
confidence: 99%